Implementasi Media ProProfs Brain Games untuk Meningkatkan Motivasi Belajar Qawaid Nahwu di Madrasah Aliyah - Ahmad Faisal Zam Ani; Intan Nur Fauziah Saputri (MAN 1 Pasuruan, 2025)
The widespread use of digital tools among the Indonesian population has created a new dimension in its cultural society. To improve the quality of educational institutions in Indonesia, teachers need to understand and implement various media provided by Google. This article aims to offer varied and effective assessment methods in teaching qawaid nahwu using ProProfs Brain Games media, which includes Word Scramble, Hangman, and Crossword. This research employs a qualitative approach with a type of library research. The data collection technique used in this research is library study, utilizing various materials available in libraries, such as books, newspapers, magazines, scripts, documentation, and other sources relevant to the research. The research results show that through several interactive games available in the ProProfs Brain Games menu, the learning process of qawaid nahwu will become more engaging and enjoyable. Word Scramble helps students understand the material and memorize the rules of Arabic nahwu better through challenging letter arrangement activities. Hangman can be used to improve students' spelling skills and understanding of qawaid nahwu in a fun and competitive way. Crossword allows students to hone their knowledge of important rules in learning nahwu by solving the given clues, which also enhances their visual literacy skills. Thus, ProProfs Brain Games is an engaging, innovative, and suitable learning medium for the assessment of qawaid nahwu learning at various educational levels.